The genome sequence of the Eurasian minnow, Phoxinus phoxinus (Linnaeus, 1758) [version 1; peer review: 2 approved, 1 approved with reservations] - Andy D. Nunn; Bernd Hänfling; Paolo Moccetti (Wellcome Open Research)
We present a genome assembly from an individual female Phoxinus phoxinus (the Eurasian minnow; Chordata; Actinopteri; Cypriniformes; Leuciscidae). The genome sequence spans 950.50 megabases. Most of the assembly is scaffolded into 25 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 18.36 kilobases in length.